Proceedings of the 52nd Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2014
DOI: 10.3115/v1/p14-1141
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Instructor's Intervention in MOOC forums

Abstract: Instructor intervention in student discussion forums is a vital component in Massive Open Online Courses (MOOCs), where personalized interaction is limited. This paper introduces the problem of predicting instructor interventions in MOOC forums. We propose several prediction models designed to capture unique aspects of MOOCs, combining course information, forum structure and posts content. Our models abstract contents of individual posts of threads using latent categories, learned jointly with the binary inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 28 publications
0
58
0
2
Order By: Relevance
“…Finally, we cite the work of Chaturvedi et al [5] that proposes a model to identify the situation when the MOOC instructor has to intervene in the forum threads. The purpose is to help students get an answer from the instructor in order to provide them with the effective knowledge they need.…”
Section: Methods Proposed To Enhance the Collaborative Learning Processmentioning
confidence: 99%
“…Finally, we cite the work of Chaturvedi et al [5] that proposes a model to identify the situation when the MOOC instructor has to intervene in the forum threads. The purpose is to help students get an answer from the instructor in order to provide them with the effective knowledge they need.…”
Section: Methods Proposed To Enhance the Collaborative Learning Processmentioning
confidence: 99%
“…Their results show that instructors' active participation can increase the discussion volume but cannot mitigate the participation decline [18]. Chaturvedi et al employed latent categories to abstract contents of posts, and utilized event chain based model to predict the instructors' intervention in MOOC discussion forum [6]. Skrypnyk et al conducted social network analysis on Twitter-based interactions and confirmed that the teachers preserved a high level of influence over the flow of information [7].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, the interaction behaviour in the forum, as a data source of learning analysis, is getting more and more attention. These topics not only include correlation between the forum participation and final gains [2]- [5], but also include the instructors' role and intervention in the forum [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…The "China Basic Education Big Data Development Blue Book (2015)" Conference and Education Big Data Summit Forum held in Beijing Normal University in 2016 [2]. In addition, according to the statistics, Coursera, edX, and Udacity which are three pioneer MOOC platforms provide thousands of courses and draw more than 100,000 registrants each course [5,6]. And Tsinghua University also officially launched the first Chinese version of the MOOC platform -"xuetangX" [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the learning process can significantly design better courses and improve the learning effect. Despite several relevant studies at present, such as, learning behavior analysis [3], student classification and engagement analysis [6,7], there are few systematical studies on the factors of affecting learning effects in online learning. More specifically, how to use the existing learning theory and data mining to observe which factors are related to students learning efficiency?…”
Section: Introductionmentioning
confidence: 99%